2007
DOI: 10.1161/strokeaha.107.487090
|View full text |Cite
|
Sign up to set email alerts
|

Risk Factors for Intracerebral Hemorrhage in a Pooled Prospective Study

Abstract: Background and Purpose-Few prospective studies have reported risk factors for intracerebral hemorrhage (ICH), and results are inconsistent. We studied risk factors for ICH in a pooled cohort of the Atherosclerosis Risk in Communities Study (ARIC) and the Cardiovascular Health Study (CHS). Methods-The ARIC cohort was recruited in 1987 to 1989 and involves 15 792 men and women, aged 45 to 64 years at baseline, sampled from 4 US communities. The CHS cohort was recruited in 1989 to 1993 and involves 5888 men and w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

22
228
5
11

Year Published

2011
2011
2021
2021

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 312 publications
(266 citation statements)
references
References 61 publications
22
228
5
11
Order By: Relevance
“…38, 39 Serum total, LDL or non-high-density lipoprotein (HDL) cholesterol levels or the LDL/HDL cholesterol ratio have been positively associated with risk of IHD, whereas HDL cholesterol levels were inversely associated with the risk. 26-28,40, 41 To predict 5-year probabilities of developing acute myocardial infarction, the non-HDL cholesterol model was found to have better predictive ability (area under the receiver-operating curve [AUC]=0.825) than the total cholesterol model (AUC=0.815).…”
Section: Trends In the Incidence Of Cvd In Japanmentioning
confidence: 99%
“…38, 39 Serum total, LDL or non-high-density lipoprotein (HDL) cholesterol levels or the LDL/HDL cholesterol ratio have been positively associated with risk of IHD, whereas HDL cholesterol levels were inversely associated with the risk. 26-28,40, 41 To predict 5-year probabilities of developing acute myocardial infarction, the non-HDL cholesterol model was found to have better predictive ability (area under the receiver-operating curve [AUC]=0.825) than the total cholesterol model (AUC=0.815).…”
Section: Trends In the Incidence Of Cvd In Japanmentioning
confidence: 99%
“…In other words, the cholesterol level is recognized to be a risk factor only for atherothrombotic cerebral infarction, and the major risk factor for all types of cerebral infarction, including atherothrombotic cerebral infarction, is hypertension 9) . Many reports in various countries, including Japan, have stated that hypocholesterolemia is a risk factor for cerebral hemorrhage 16,25) . A meta-analysis of cohort studies found that a decrease in the cholesterol level by 1 mmol/L (38.6 mg/dL) is associated with an increase in the frequency of cerebral hemorrhage of 19% 21) .…”
Section: Measures To Prevent Cerebrovascular Diseasementioning
confidence: 99%
“…Despite the association of low cholesterol levels [122,123] and the use of a statin with ICH [124], there is a growing interest in the pleiotropic effects of the 3-hydroxy-3-methylglutaryl coenzyme A reductase inhibitors (i.e., statins). The promising neuroprotective benefit of the statins in acute ischemic stroke [125][126][127] has led to a similar evaluation in ICH models.…”
Section: Anti-inflammatory Agents: Statinsmentioning
confidence: 99%